Time Pattern of Male-Female Wage Differentials : Ontario 1946-71 - Gunderson, Morley (Relations industrielles / Industrial Relations, 1976)
In this paper the author examines whether male-female wage differentials have narrowed over time, whether such differentials narrow or widen at the peak of a business cycle, and whether the stricter enforcement of equal pay legislation in recent years has influenced these differentials.